Cladribine vs other drugs in MS: Merging randomized trial with real-life data. Issue 6 (November 2020) - Signori, Alessio; Saccà, Francesco; Lanzillo, Roberta; Maniscalco, Giorgia Teresa; Signoriello, Elisabetta; Repice, Anna Maria; Annovazzi, Pietro; Baroncini, Damiano; Clerico, Marinella; Binello, Eleonora; Cerqua, Raffaella; Mataluni, Giorgia; et al.
Abstract : Objective: Cladribine tablets were tested against placebo in randomized controlled trials (RCTs). In this study, the effectiveness of cladribine vs other approved drugs in patients with relapsing-remitting MS (RRMS) was compared by matching RCT to observational data. Methods: Data from the pivotal trial assessing cladribine tablets vs placebo (CLARITY) were propensity score matched to data from the Italian multicenter database i-MuST. This database included 3, 150 patients diagnosed between 2010 and 2018 at 24 Italian MS centers who started a disease-modifying drug. The annualized relapse rate (ARR) over 2 years from treatment start and the 24-week confirmed disability progression were compared between patients treated with cladribine and other approved drugs (interferon, glatiramer acetate, fingolimod, natalizumab, and dimethyl fumarate), with comparisons with placebo as a reference. Treatment effects were estimated by the inverse probability weighting negative binomial regression model for ARR and Cox model for disability progression. The treatment effect has also been evaluated according to baseline disease activity. Results: All weighted baseline characteristics were well balanced between groups. All drugs tested had an effect vs placebo close to that detected in the RCT. Patients treated with cladribine had a significantly lower ARR compared with interferon (relapse ratio [RR] = 0.48; p < 0.001), glatiramer acetate (RR = 0.49; p < 0.001), and dimethyl fumarate (RR = 0.6; p = 0.001); a similar ARR to that with fingolimod (RR = 0.74; p = 0.24); and a significantly higher ARR than natalizumab (RR = 2.13; p = 0.014), confirming results obtained by indirect treatment comparisons from RCTs (network meta-analyses). The relative effect of cladribine tablets 10 mg (cumulative dose 3.5 mg/kg over 2 years) was higher in patients with high disease activity vs all treatments except fingolimod and natalizumab. Effects on disability progression were largely nonsignificant, probably due to lack of power for such analysis. Conclusion: In patients with RRMS, cladribine tablets showed lower ARR compared with matched patients who started interferon, glatiramer acetate, or dimethyl fumarate; was similar to fingolimod; and was higher than natalizumab. The beneficial effect of cladribine tablets was generally amplified in the subgroup of patients with high disease activity. Classification of evidence: This study provides Class III evidence that for patients with RRMS, cladribine-treated patients had lower ARR compared with interferon, glatiramer acetate, or dimethyl fumarate; similar ARR compared with fingolimod; and higher ARR compared with natalizumab.